Yacon meal (Smallanthus sonchifolius) as prebiotic in rations of Muscovy (Cairina moschata) ducks during the fattening phase - Fuentes N., Nadia (2012)
The purpose of the study was to evaluate the effect of yacon meal as a prebiotic in rations for Muscovy ducks. One hundred and fifty male ducks of seven weeks of age were used. The ducks were grouped in five treatments: T0, control (without yacon and antibiotic); T1, zinc bacitracin 0.035%; T2, T3 and T4, yacon meal at 0.25, 0.50 and 0.75% respectively. Treatments T1, T2 and T4 resulted in higher body weight gain as compared to T0 (p<0.05). No differences were observed between treated groups and T0 on feed consumption. Feed conversion index was significantly better in T1, T3 and T4 as compared to T0 (p<0.05). The cost of feed per unit of body weight gain was lower in T1, T2, T3 and T4 as compared to T0. The inclusion of 0.75% of yacon meal in the diet would be an alternative to the use of antibiotics in rations of ducks during the fattening phase.